Knowledge, Productivity, and Innovation in Nigeria : Creating a New Economy - Radwan, Ismail; Pellegrini, Giulia (World Bank, 2012)
Harnessing knowledge for development is not a new concept. Knowledge has always been central to development and can mean the difference between poverty and wealth. The knowledge economy is not just about establishing high-tech industries and creating an innovative and entrepreneurial culture. Economic literature indicates that simply adopting existing technologies widely available in developed countries can dramatically boost productivity and economic growth. This paper highlights the knowledge economy (KE) issues that confront Nigeria and offers policy prescriptions that will allow the country to take advantage of the opportunities available in moving toward a knowledge-based economy. The Knowledge Assessment Methodology (KAM) developed by the World Bank considers four pillars: a) skills and education, b) business environment, c) information and communications infrastructure, and d) innovation system.